Acute Oral Toxicity of Banggai Yam Flour Extract (Dioscorea alata) in Mice (Mus musculus) - Sattu, Marselina; Syahrir, Muh; Gunawan, NHD (Journal of Health and Nutrition Research, 2025)
Banggai yam (Dioscorea alata), a local tuber cultivated in Central Sulawesi, Indonesia, is known for its rich nutritional content, including complex carbohydrates, dietary fiber, essential vitamins, minerals, and bioactive compounds such as anthocyanins and polyphenols. Although its nutritional potential has been well documented, its consumption safety, especially in processed forms such as powdered extract, requires toxicological validation. This study aimed to evaluate the acute oral toxicity of Banggai yam powdered extract using a murine model. This study had three treatment groups that received Banggai yam flour extract at different doses (1.95 g, 3.906 g, and 5.9 g) and one control group that received 1% CMC Na. Observations and measurements were analyzed using independent sample t-tests through SPSS software. The analysis did not show statistically significant differences between the treatment and control groups, with p-values of 0.55, 0.97, and 0.85, respectively. These findings indicate that Banggai yam extract does not produce acute toxic effects at the dose levels tested. In conclusion, in animal models, Banggai yam flour extract is considered non-toxic under acute exposure conditions. Further studies involving subchronic and chronic toxicity tests and evaluation in human subjects are recommended to confirm its broader safety profile and support its use as a functional food ingredient.